(untitled) (Research, Society and Development, 2022)
Introduction: Epilepsy is a brain dysfunction characterized by the periodic and unpredictable occurrence of seizures, which are temporary changes in behavior caused by abnormal, disordered, synchronous and rhythmic neuronal activity. Cannabidiol acts as an anticonvulsant through three mechanisms: neuroprotection, stress modulation, or even the neuronal excitation/inhibition balance. Objective: To describe aspects related to the treatment of epilepsy with Cannabidiol and derivatives. Methodology: Systematic review following the guidelines described in the PRISMA method. A search was carried out in the following databases: PUBMED, BVS and SciELO using the terms: “cannabidiol”, “CNB”, “epilepsy”, “epilepsy” and “cannabidiol” as descriptors, which were combined with the connector “ and”. Primary studies were included, in full, published during the period from 2012 to 2022, in Portuguese or English, which addressed the theme related to the isolated use of Cannabidiol in the treatment of Epilepsy. Results: 12 articles were included to compose this systematic review, which demonstrated a clinically significant reduction in seizures after treatment with cannabidiol. Most studies addressed Lennox-Gastaut or Dravet syndrome, while other trials addressed treatment-resistant epilepsies of different diagnoses. The most used dose was 20 mg/kg/day and 10 mg/kg/day. Conclusion: Cannabidiol is effective in reducing and controlling seizures in different pathologies. It is safe and effective for adult and pediatric use. It produces an effect both at higher doses (20mg/kg/day) and at low doses (10mg/kg/day).